Nursing Home Study, 1987-1992 - Braithwaite, John (ADA Dataverse, 2019)
The Nursing Home Study was undertaken with the broad aim of achieving a better understanding of implementation of the nursing home outcome standards, which the Commonwealth government introduced in July 1987. The study was partially funded by the Department of Community Services and Health, and was undertaken in nursing homes in the states of Victoria, New South Wales, Queensland and South Australia. The study sampled two populations, directors of nursing (DON) and standards monitoring team (SMT) members. Variables were similar for each of the sampled populations and included hierarchical structure of the nursing home; committees within the nursing home; perceptions of the ratings given by SMT of the nursing home; perceptions of the standards; perceived costs of meeting the standards; and perceptions of the SMT. Background variables include state; sex; employment status; occupation and educational attainment.